Two-dimensional adaptive perfect reconstruction filter banks using lifting scheme = Dvodimenzionalni adaptivni filtarski slogovi s potpunom rekonstrukcijom realizirani metodom podizanja : master thesis = magistarski rad - Vrankić, Miroslav; Seršić, Damir (Zagreb : N. Vrankić ; Fakultet elektrotehnike i računarstva, 2003)
Ključne riječi: wavelet ﬁltarski slogovi, waveleti druge generacije, multirezolucijska analiza, adaptivna shema podizanja, quincunx polifazno razlaganje, neseparabilni ﬁltri, interpolacijski ﬁltri, rekonstrukcija slike s gubicima.
More efﬁcient coding, modelling and image analysis generate the need for search for better methods of the multiresolution image analysis, i.e. for more efﬁcient wavelet ﬁlter bank structures. This thesis is based on a previous research of one-dimensional ﬁlterbankstructuresthathadthepossibilitytoadaptﬁlterparameterstotheproperties of the analyzed signal. In this thesis we present the construction of a two-dimensional adaptive wavelet ﬁlter bank that is based on a lifting scheme. The ﬁlter bank is nonseparable, based on a quincunx polyphase decomposition and nonseparable ﬁlters. The lifting scheme has beenchosensinceitallowsforaneasyconstructionofspacevaryingﬁlterbankswitha perfectreconstructionproperty. Theproposedﬁlterbankadaptstotheanalyzedimage foreverypixelinalldecompositionlevelswhilestillpreservingthegoodpropertiesof the wavelet decomposition. A number of vanishing moments is guaranteed by the ﬁxed part of the ﬁlter bank. Without degrading the overall ﬁlter bank properties, the variable part can be changed in order to adapt to the analyzed image. The paper explores various one-dimensional and two-dimensional adaptation methods based on the least squares criterion. Adaptation results have been shown for a number of synthetic and real-world images. Effects of lossy image reconstruction and impact of ﬁlter coefﬁcients’ quantization to the efﬁciency of the image decomposition have been presented.
Keywords: wavelet ﬁlter banks, second generation wavelets, multiresolution analysis, adaptive lifting scheme, quincunx polyphase decomposition, nonseparable ﬁlters, interpolating ﬁlters, lossy image reconstruction
Bibliografija str. 113-115.